Cultivating global antimicrobial stewardship: Linguistic and cultural validation of the Australian National Antimicrobial Prescribing Survey appropriateness assessment definitions for Portugal - Palos, C. (2024)
Background Antimicrobial resistance is driven by inappropriate antimicrobial prescribing. The National Antimicrobial Prescribing Survey (NAPS) is an Australian-developed auditing platform to assist in the assessments of antimicrobial quality by antimicrobial stewardship programmes using consensus-based definitions. The NAPS has demonstrated to be transferable to other countries. Its adaptation to Portugal could improve knowledge about the quality of antimicrobial prescribing in the country. Objectives To translate, culturally adapt, and validate the Australian Hospital NAPS appropriateness assessment definitions of antimicrobial prescribing for Portugal. Methods International recommendations on translation and adaptation of instruments were followed. Two panels of experts participated in the process, using Zoom® for discussions and interviews, and Google Forms® for assessing vignettes. A native English-speaking person proficient in Portuguese conducted the back-translation. SPSS v.28 and Excel® were used for validity calculation. Results The Portuguese version was well accepted, its implementation being perceived as desirable and feasible by the experts. Validation process showed a Fleiss’ ? score of 0.483 (95% CI, 0.415–0.551, P < 0.005) for appropriateness, and an average agreement with the Australian NAPS team of 0.8 and 0.9, respectively, for appropriateness and reasons for inappropriateness. Conclusions The Portuguese version of the Australian Hospital NAPS appropriateness assessment definitions of antimicrobial prescribing, the first to be translated from English, was deemed non-inferior to the original, was well accepted, considered to be desirable and feasible, and could inspire other countries, particularly other Portuguese-speaking countries, to adapt and validate them in their own contexts, reinforcing the possibility of transferring NAPS use beyond Australia.